Cell Death in the Epithelia of the Intestine and Hepatopancreas in Neocaridina heteropoda (Crustacea, Malacostraca). - Lidia Sonakowska; Agnieszka Włodarczyk; Grażyna Wilczek; Piotr Wilczek; Sebastian Student; Magdalena Maria Rost-Roszkowska (PLoS ONE, 2016)
The endodermal region of the digestive system in the freshwater shrimp Neocaridina heteropoda (Crustacea, Malacostraca) consists of a tube-shaped intestine and large hepatopancreas, which is formed by numerous blind-ended tubules. The precise structure and ultrastructure of these regions were presented in our previous studies, while here we focused on the cell death processes and their effect on the functioning of the midgut. We used transmission electron microscopy, light and confocal microscopes to describe and detect cell death, while a quantitative assessment of cells with depolarized mitochondria helped us to establish whether there is the relationship between cell death and the inactivation of mitochondria. Three types of the cell death were observed in the intestine and hepatopancreas-apoptosis, necrosis and autophagy. No differences were observed in the course of these processes in males and females and or in the intestine and hepatopancreas of the shrimp that were examined. Our studies revealed that apoptosis, necrosis and autophagy only involves the fully developed cells of the midgut epithelium that have contact with the midgut lumen-D-cells in the intestine and B- and F-cells in hepatopancreas, while E-cells (midgut stem cells) did not die. A distinct correlation between the accumulation of E-cells and the activation of apoptosis was detected in the anterior region of the intestine, while necrosis was an accidental process. Degenerating organelles, mainly mitochondria were neutralized and eventually, the activation of cell death was prevented in the entire epithelium due to autophagy. Therefore, we state that autophagy plays a role of the survival factor.